The Logical Pattern of Argument: A Case Study of National University Debating Championship - Supardi, Moh.; Sayogie, Frans (Elsya : Journal of English Language Studies, 2022)
In academic field, argument is an essential factor of understanding statements. In this regard, the present paper aims to analyse National University Debate Contest (NUDC) 2016 using Toulmin model argumentative structure and its relation with the implied meaning from National University Debate Contest. This paper employs descriptive qualitative analysis to examine the logical pattern of arguments through linguistic expressions that occurred in the debate. The data were taken from NUDC in Mercu Buana University focusing on (part 1) the statement of the government proponent (Bina Nusantara University) and the opposite speaker (Brawijaya University). The data were analysed using the Toulmin model of logical argument. The findings showed that the government opposite speaker very often made the rebuttal claim by showing the weaknesses from the government side; while the government proponent speaker has claimed almost in every pattern of argument proposed by Toulmin model. The paper concludes that both speakers’ patterns of argument have utilized Toulmin model such as claims, data, qualifiers, rebutting conditions, and warrants. Even though there are so many grammatical mistake and unwell-organized structure, but the logical structure can be analysed using Toulmin model.